2019
DOI: 10.1186/s12864-018-5388-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the differential mechanisms of carotenoid biosynthesis in the yellow peel and red flesh of papaya

Abstract: BackgroundRed-fleshed papaya is a good material to study the different carotenoids accumulation mechanism in the peel and flesh. Although the peel and flesh of papaya closely integrated into one body, the flesh coloration changing from white to red, while the exocarp coloration changing from green to yellow. In this study, the major carotenoids accumulation and the expression patterns of key carotenoid biosynthesis pathway genes in the process of papaya fruit ripening were studied, and the carotenoid biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 38 publications
1
48
0
1
Order By: Relevance
“…Another MYB transcription factor, GOLDEN2-LIKE (GLK2), was shown to enhance lycopene levels in tomato fruit at the red ripe stage [43,44], [45]. Here, we identified twenty-four WRKY and nine bHLH transcription factors, which have also been implicated in papaya fruit carotenoid biosynthesis [46], but their regulatory roles are still unknown. In the current study we identified a number of transcription factors, such as MADS14, NAC25, MYB1R1, MYB21, MYB44, MYC2, GLK1 and GLK2, that are likely involved in carotenoid metabolism in apricot fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Another MYB transcription factor, GOLDEN2-LIKE (GLK2), was shown to enhance lycopene levels in tomato fruit at the red ripe stage [43,44], [45]. Here, we identified twenty-four WRKY and nine bHLH transcription factors, which have also been implicated in papaya fruit carotenoid biosynthesis [46], but their regulatory roles are still unknown. In the current study we identified a number of transcription factors, such as MADS14, NAC25, MYB1R1, MYB21, MYB44, MYC2, GLK1 and GLK2, that are likely involved in carotenoid metabolism in apricot fruit.…”
Section: Discussionmentioning
confidence: 99%
“…Yellow pulp varieties are characterized by the presence of these last carotenoids with very low to no detectable levels of lycopene (Shen et al., 2019). As the metabolism of papaya carotenoids starts from phytoene and occurs in a well-known cascade process (Figure 3B), it is possible to establish a relationship between the pattern of enzymes that acts downstream to phytoene and the color of papaya pulp during ripening.…”
Section: Pulp Color Changes In Ripening Papayas As a Consequence Of Cmentioning
confidence: 99%
“…RNA sequencing (RNA-Seq) technology has provided unique insights into the molecular characteristics of non-model organisms without a reference genome, and a series of genes involved in flavonoid pigment biosynthesis and carotenoid biosynthesis have been systematically analyzed [1,33,34]. However, the limitations of short-read sequencing lead to a number of computational challenges and hamper transcript reconstruction and the detection of splice events [35].…”
Section: Introductionmentioning
confidence: 99%